The Servant Leadership of School Administrator and Quality of Work Life of Teacher under the Secondary Educational Service Area Office 9 - Bonrod, Tipsukon; Wangthanomsak, Mattana (Arts of Management Journal, 2021)
The purposes of this research were to determine 1) the servant leadership of school administrator under the Secondary Educational Service Area Office 9 2) the quality of work life of teacher under the Secondary Educational Service Area Office 9 and 3) the relationship between the servant leadership of school administrator and quality of work life of teacher under the Secondary Educational Service Area Office 9. The research of descriptive research. The population and sample of this research were 56 schools under the Secondary Educational Service Area Office 9. The respondents in each school consisted of 2 persons: school director and teacher with the total of 112. The research instrument was a opinionnaire regarding the servant leadership of school administrator based on the concept of Greenleaf and the quality of work life of teacher based on the concept of Cummings and Worley. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation and Pearson’s product moment correlation coefficient. The research findings revealed that: 1) The servant leadership of school administrator under the Secondary Educational Service Area Office 9 as a whole and as an individual, was at a high level. 2) The quality of work life of teacher under the Secondary Educational Service Area Office 9 as a whole and as an individual, was at a high level. 3) The relationship between the servant leadership of school administrator and quality of work life of teacher under the Secondary Educational Service Area Office 9 was found statistically significant at .01 level.